HARTA BUANG: : ANTARA PENGHARGAAN TERHADAP WANITA TANIMBAR DAN PERGESERAN ALAT PEMBAYARAN - Seralarat, Kornelis; Batlayeri, Willem (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STPAK St. Yohanes Penginjil Ambon, 2017)
Harta buang is a customary fine, such as ivory, male earrings and gold breast pendant, to be paid by the divorcing party of the husband or wife. Harta buang also means a fine to be paid to the woman who was raped, humiliated, or made a temporary lover but then not married. These customary treasure fines are intended to prevent the occurrence of divorce and also as a form of expression of restoration and respect for the dignity of women who have been divorced or abused. This study aims to describe Tanimbarese people’s understanding of the shift in the means of payment of property and their appreciation of women. The results show that people of Tanimbar began to use money as a means of payment of the property as determined by the officials of Tanimbarese villages (latupati). The villages’ officials of Tanimbarese were of the opinion that paying both with customary objects and with money express the respect for women. However, some Tanimbarese still consider that payments with customary objects are more wighted and beter respect for women.